Association of menopausal symptoms with sociodemographic factors and personality traits - Augoulea, A.; Moros, M.; Kokras, N; Karageorgiou, V.; Paschou, S. A.; Lymberi, R.; Panoulis, K.; Kaparos, G.; Lykeridou, A.; Lambrinoudaki, I. (Prz Menopauzalny, 2019)
AIM OF THE STUDY: To investigate the association of personality traits with the severity of vasomotor symptoms (VMS) in a predominantly Greek population. MATERIAL AND METHODS: A questionnaire-based study of women from the Menopause Clinic of a University Hospital in Athens, Greece. Sociodemographic parameters were documented through a structured interview. All women completed the Menopause Rating Scale (MRS) for the assessment of severity of menopausal symptoms, the Hot Flush Beliefs Scale (HFBS) for the assessment of how women were coping with their symptoms and the Big Five Inventory questionnaires for the assessment of personality traits. Associations between baseline parameters and menopausal symptoms were assessed with univariate and multivariate regression analyses. RESULTS: One hundred women were included. Employed women had lower MRS sub-scores (psychological p< 0.001, somatic p< 0.047, urogenital p< 0.008). Married women scored higher in the psychological and somatic domains. Women of university educational level coped significantly better with hot flushes (β coefficient [SE]: 0.72 [0.25], p< 0.01) and night sweats (0.57 [0.19], p< 0.01) than women of primary education, although the significance of these findings was not replicated when taking into account confounders. Regarding personality traits, women with low openness (-0.33 [0.11], p< 0.01) and empathy (-0.83 [0.37], p = 0.03) and high agreeableness (1.13 [0.21], p< 0.001) had more severe menopausal symptoms. In contrast, women with high agreeableness could better cope with their menopausal symptoms (-0.75 [0.36], p = 0.04). These associations were independent of sociodemographic factors. CONCLUSIONS: Personality traits, especially agreeableness, openness and empathy are associated with menopausal symptoms and functionality in postmenopausal women. These associations might serve as indicators of women at risk of experiencing more severe VMS.
Keywords: climacteric; menopause; personality; sociodemographic; symptoms